Flow diverting devices in acute ruptured blood blister aneurysms: a three centric retrospective study - Incandela, Francesca; Craparo, Giuseppe; Abrignani, Sergio; Tessitore, Agostino; Pitrone, Antonio; Caranci, Ferdinando; Arrichiello, Antonio; Paolucci, Aldo (Acta Biomedica Atenei Parmensis, 2020)
Background: Blood blister aneurysms (BBAs) are a rare tiny subset of intracranial aneurysms, located at the nonbranching site of an artery, representing a therapeutic challenge from both surgical and endovascular approach. Flow-diverting efficacy, by preserving flow through the parent artery, was approved for its use in unruptured cerebral aneurysms, but no consensus was reached on its use for BBAs ruptured in the acute setting. We report a multicenter experience of use of flow diversion in acute setting of ruptured BBA, to analyze the safety and efficacy of these devices. Methods: We performed a retrospective study of 6 consecutive intracranial BBAs treated with flow diverter devices (FDD) between 2018 and 2020 at 3 italian institutions. Materials, therapy used, complications, clinical and radiographic outcomes were reviewed. Results: We used different FDD, in all cases immediate change in contrast opacification at the end of the procedure was reported. Intraprocedural IIb/IIIa inhibitor agent was the major antiplatelet protocol administered. Any complications occurred. All patients showed complete BBA obliteration at 3 months follow-up. 5/6 patients achieved good clinical outcome (0–2 mRS) at 3 months, all of which were presented with low grade SAH (Hunt Hess I–III) and a lower Fisher grade. Conclusion: Our data support this endovascular technique as a safe and effective therapeutic modality for this pathology in the acute setting.